Pharmacovigilance insights: safety profiles of antifungal agents for invasive aspergillosis - Jia, Wei; Wang, Tiezhou; Wang, Jingru (Frontiers in Pharmacology, 2026)
BackgroundInvasive aspergillosis (IA) poses significant mortality risks, particularly in immunocompromised patients. The safety profiles of FDA-approved antifungal agents, triazoles (Voriconazole, Posaconazole, Isavuconazole), polyenes (Amphotericin B), and echinocandins (Caspofungin), are not yet fully characterized in real-world settings. This study employed pharmacovigilance data to systematically evaluate the comparative safety profiles of these agents, providing evidence-based insights for clinical practice.MethodsA retrospective analysis of the FDA Adverse Event Reporting System (FAERS) data (2004Q1–2024Q3) was conducted. Disproportionality analyses, including reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma-Poisson Shrinker (MGPS), were employed to identify adverse event (AE) signals. Duplicate entries were identified and removed using CASE_ID and FDA_DT criteria, after which AE signals were classified according to MedDRA System Organ Classes (SOCs) and Preferred Terms (PTs).ResultsAmong 26,004 antifungal-associated AE reports, Amphotericin B exhibited the strongest renal toxicity signals (nephropathy toxic (i.e., nephrotoxicity): ROR = 24.86; renal tubular disorder: ROR = 46.46), while voriconazole was associated with hepatobiliary disorders (ROR = 4.61) and ocular toxicity (toxic optic neuropathy: ROR = 228.80). Caspofungin demonstrated marked hepatotoxicity (cholestasis: ROR = 23.79), whereas Posaconazole and Isavuconazole showed lower mortality rates (19.56% and 22.70%, respectively). Amphotericin B demonstrated the highest mortality rate (47.14%), which was statistically significantly higher compared to other agents (χ2 test, p < 0.001), and life-threatening AE rates (4.97%), contrasting with Isavuconazole’s favorable safety profile (1.89% life-threatening AEs). Time-to-onset analysis revealed delayed AE onset for Isavuconazole (median: 19.5 days) versus Caspofungin (6 days).ConclusionSignificant safety variations exist among antifungal agents for IA. Amphotericin B and Caspofungin are associated with severe renal/hepatic toxicities and higher mortality, while Isavuconazole and Posaconazole may offer safer alternatives with delayed AE onset. Clinicians should prioritize drug-specific risks when tailoring treatment for IA patients.